Denaturation of proteins with beta-barrel topology induced by guanidine hydrochloride. Issue 3 (2010) - Stepanenko, Olesya V.; Kuznetsova, Irina M.; Verkhusha, Vladislav V.; Staiano, Maria; D'Auria, Sabato; Turoverov, Konstantin K.
Abstract : The stability of the representatives of two protein classes with β -barrel topology: porcine odorant-binding protein (OBP) and a number of fluorescent proteins (FPs), was studied. It was shown that both of them are significantly more stable than globular α-helical and α / β proteins. At the same time the value of energy barrier between native and unfolded state for FPs exceeds that for OBP. It was found that the small guanidine hydrochloride concentrations induce local structural disturbances in proteins: changes in microenvironment of tryptophan residue in the case of odorant-binding protein and decrease in chromophore non-planarity in the case of green fluorescent protein.